2018
DOI: 10.1139/cjfas-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution meets invasive species control: the potential for pesticide resistance in sea lamprey

Abstract: Rapid evolution of pest, pathogen, and wildlife populations can have undesirable effects, for example, when insects evolve resistance to pesticides or fishes evolve smaller body size in response to harvest. A destructive invasive species in the Laurentian Great Lakes, the sea lamprey (Petromyzon marinus) has been controlled with the pesticide 3-trifluoromethyl-4-nitrophenol (TFM) since the 1950s. We evaluated the likelihood of sea lamprey evolving resistance to TFM by (i) reviewing sea lamprey life history and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 140 publications
1
33
0
Order By: Relevance
“…Results from sampling just over 200 larvae from DC (a) are consistent with previous studies that indicate sea lamprey display a polygamous mating behavior (Gilmore, ; Rodrıguez‐Munoz & Tregenza, ), and (b) showed that downstream dispersal is a continuous process for individuals of different ages (Derosier et al, ). Population genetic analyses demonstrate that the SNPs developed from larval sea lampreys from two populations were variable across the Great Lakes and exhibit levels of interpopulation variance in allele frequency that are comparable to mtDNA (Waldman et al, ) and microsatellite analyses (Bryan et al, ).Identification of outlier loci (Figure ; features detailed in GitHub repository) portends developments in areas of gene‐assisted control (McCauley et al, ), for example, the exploration of potential rapid evolution in response to intense selection associated with pesticide treatments (Dunlop et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from sampling just over 200 larvae from DC (a) are consistent with previous studies that indicate sea lamprey display a polygamous mating behavior (Gilmore, ; Rodrıguez‐Munoz & Tregenza, ), and (b) showed that downstream dispersal is a continuous process for individuals of different ages (Derosier et al, ). Population genetic analyses demonstrate that the SNPs developed from larval sea lampreys from two populations were variable across the Great Lakes and exhibit levels of interpopulation variance in allele frequency that are comparable to mtDNA (Waldman et al, ) and microsatellite analyses (Bryan et al, ).Identification of outlier loci (Figure ; features detailed in GitHub repository) portends developments in areas of gene‐assisted control (McCauley et al, ), for example, the exploration of potential rapid evolution in response to intense selection associated with pesticide treatments (Dunlop et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The single largest determinant of whether resistance takes a comparatively short (e.g., 30 years) or longer time (e.g., 80 years) to develop is the annual number of tributaries treated. Across all Great Lakes, sea lamprey have been treated with TFM for an average of 50 years 34 , which is towards the beginning of when our model predicts resistance will evolve. As such, sea lamprey in the Great Lakes could be in the incipient stages for the evolution of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This longevity means that sea lamprey generation times are longer and their response to selection slower in real time in comparison with many other pest species. Assuming an average generation time of between 3 and 5 years, invasive sea lamprey may have been exposed to TFM for 20-30 generations, which may not be sufficient time for resistance to evolve (but see 3436 ). Another reason that resistance may not evolve is the high rate of dispersal and subsequent gene flow found in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Since the application of TFM to locations with abundant larval lamprey, invasive sea lamprey populations have declined by up to 90% (Heinrich et al, 2003; Smith & Tibbles, 1980). However, TFM applications kill most, but not all, larval sea lamprey (Dunlop et al, 2017) and it is possible that resistant individuals could survive and reproduce. If this process is repeated over enough generations, then resistant individuals could increase in frequency – a scenario documented in many systems where pests have been controlled by chemical means (Whalon, Mota-Sanchez, & Hollingworth, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…If this process is repeated over enough generations, then resistant individuals could increase in frequency – a scenario documented in many systems where pests have been controlled by chemical means (Whalon, Mota-Sanchez, & Hollingworth, 2008). The evolution of resistance would greatly reduce the effectiveness of TFM, which is currently the primary control method for invasive sea lamprey (Dunlop et al, 2017), and decreased pesticide effectiveness would likely hamper the restoration of native and commercially-important fish populations throughout the Great Lakes.…”
Section: Introductionmentioning
confidence: 99%